Crescimento e produção da candeia em plantio sujeito a diferentes espaçamentos e podas - Silva, Charles Plínio de Castro (2009)
This work analyzed the behavior of diameter, height, crown area and volume variables, in each stem and per hectare, of candeia plantation, subject to different spacing and pruning. The experiment of subdivided parcels in strips was installed in March 2002, in Carrancas county-MG- with seedlings supplied by the local EMATER, at 4 planting spacing (T01-1,5x1,5m, T02-1,5x2,0m, T03- 1,5x2,5m and T04-1,5x3,0m), and sub parcels with and without pruning, being inventoried 896 planting holes of useful area by spacing, in 4 blocks. The measurements were made every six months to evaluate if the height of all the plants and the circumference at 1.30m height (CBH) of those stems possessing CBH≥9.0 cm. The crown area was measured annually, starting from the third year. As initial result, the data were classified according to the time of measurement of minimum CBH; in other words, the group of stems in which minimum CBH was measured at 1.92 years was analyzed separately. The same procedure was adopted for measuring the stems starting from 2.58 years old, 3.08 years old, 3.67 years old, 4.08 years old, 4.58 years old, 5.08 years old and 6.5 years old, besides the stems that didn't have the measured CBH. The different spacing of the experiment didn't affect, statistically, at 6.5 years, the diameter at 1,30m of height, the total height, the stem volume and the volume per hectare. The pruning answered positively to the growth when DBH and stem volume were analyzed. When the total height and volume per hectare were analyzed, the pruning presented positive result only at the 1.5 x 1.5m spacing.